Incision wound healing test ethanolic extract gel from Ekor Naga (Rhaphidophora pinnata (L.f) Schott) leaves in white male rats - Fathnur Sanik; Havizur Rahman; Ave Olivia Rahman; Agung Giri Samudra; Cassa de Floris; Muhaimin Muhaimin (Pharmaciana, 2022)
Ekor naga (Rhaphidophora pinnata (L.f) Schott) leaves have been researched and tested. So, it was known that the chemical content of secondary metabolites effect wound healing. This study aimed to determine the gel effect of ekor naga leaves extracts as a wound healing medicine. The research method evaluated organoleptic, pH, spreadability, and adhesion of gel preparations which were measured every week for four weeks. The testing of gel effect on the wound healing medicine was being performed. In 5 treatment groups namely positive control: Bioplasenton, Formula 0: negative control, Formula 1: 10% extract concentration, Formula 2: 15% extract concentration, and Formula 3: 20% extract concentration. The result obtained were analyzed by one-way ANOVA and continued by the Duncan test with a level of 95% confidence. The research results showed that formula 3 has the best wound healing effect, followed by formulas 2 and 1. The statistical results have a significant difference (p<0,05), but the results of stability observations of the formula two preparation have a stable. Evaluation value for four weeks of observation with a care effect of 95.3%. So, formula 2 is the best formula for stability and testing wound healing effectiveness.